Applications of Maxwell's Equations - Cochran, John F.; Heinrich, Bretislav (Open textbook library., 2020)
This book was developed at Simon Fraser University for an upper-level physics course. Along with a careful exposition of electricity and magnetism, it devotes a chapter to ferromagnets. According to the course description, the topics covered were “electromagnetics, magnetostatics, waves, transmission lines, wave guides,antennas, and radiating systems.”